2009
DOI: 10.1111/j.1465-3362.2008.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Is socioeconomic status in early life associated with drug use? A systematic review of the evidence

Abstract: We found consistent, though weak, evidence to support the assumption that childhood disadvantage is associated with later cannabis use. Further research is needed to clarify this issue and to inform future policies and public health messages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 27 publications
5
73
0
6
Order By: Relevance
“…Age, sex, birth cohort (three dummy variables representing four 20-year time intervals), and ten genetic PCs (three ancestry-informative PCs and seven PCs accounting for genotyping batch effects) were included as covariates in the model. Analyses also accounted for two environmental factors (level of urbanisation and socio-economic status) that have previously been found to be associated with schizophrenia and cannabis use (Daniel et al, 2009; Kuepper et al, 2011; Martino et al, 2008; Vassos et al, 2012; Werner et al, 2007). Based on postal code, we determined the level of urbanisation of participants’ residence (ranging from 1 (very high, >2500 addresses per km 2 ) to 5 (very low, <500 addresses per km 2 ) and socio-economic status as measured by the average income of their residential area.…”
Section: Methodsmentioning
confidence: 99%
“…Age, sex, birth cohort (three dummy variables representing four 20-year time intervals), and ten genetic PCs (three ancestry-informative PCs and seven PCs accounting for genotyping batch effects) were included as covariates in the model. Analyses also accounted for two environmental factors (level of urbanisation and socio-economic status) that have previously been found to be associated with schizophrenia and cannabis use (Daniel et al, 2009; Kuepper et al, 2011; Martino et al, 2008; Vassos et al, 2012; Werner et al, 2007). Based on postal code, we determined the level of urbanisation of participants’ residence (ranging from 1 (very high, >2500 addresses per km 2 ) to 5 (very low, <500 addresses per km 2 ) and socio-economic status as measured by the average income of their residential area.…”
Section: Methodsmentioning
confidence: 99%
“…IDUs have more possibilities to grow-up and continue to live in poverty and of high crime rate neighborhoods, with fewer opportunities to have a job and health insurance coverage, with limited or absent social support [43]. As a result they live marginalized in the boundaries of their community and have little chance of access to HCV treatment, to drug-addiction services and finally little prospect to live a healthy and prosperous life [49]. Of course in the context of socio-ecologic model, broader contexts such as the effectiveness of the health system and the social policies implemented are also affecting this group [50].…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, Benjet et al [9] found no significant association between family socioeconomic status (F-SES) and any illicit drug use during life. In a recent review, Daniel et al [10] concluded that cannabis use and family social background were weakly and inconsistently related.…”
mentioning
confidence: 98%